2021
DOI: 10.1007/s11001-021-09440-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle breakage on the shear strength of calcareous sands

Abstract: The particle breakage of calcareous sands plays a key role in determining the particle shape and shear strength. This process has been analysed in the current study by employing the ring shear tests on calcareous sands sampled from the South China Sea. In this study, a set of parameters, e.g. roundness and aspect ratio, have been employed to quantify the geometrical properties of calcareous sands pre- and after the breakage. These two parameters have been found to correlate well with the vertical loading stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The analytical results (Eqs. 8, 9, and 10) obtained using the fitting parameters, including ๐›ผ ๐‘ฅ = 1, ๐ท ๐‘ฅ = 0.1, and ๐œŒ ๐‘  = 2.742 g/cm 3 , demonstrate a good agreement with the experimental results. This validation further confirms that as particle size decreases, the particle porosity decreases as well, indicating that the crushing process exposes intra-particle voids and leads to a reduction in particle porosity.…”
Section: Dry Density Porosity and Void Ratio Of Soil Particlesupporting
confidence: 74%
See 3 more Smart Citations
“…The analytical results (Eqs. 8, 9, and 10) obtained using the fitting parameters, including ๐›ผ ๐‘ฅ = 1, ๐ท ๐‘ฅ = 0.1, and ๐œŒ ๐‘  = 2.742 g/cm 3 , demonstrate a good agreement with the experimental results. This validation further confirms that as particle size decreases, the particle porosity decreases as well, indicating that the crushing process exposes intra-particle voids and leads to a reduction in particle porosity.…”
Section: Dry Density Porosity and Void Ratio Of Soil Particlesupporting
confidence: 74%
“…The microscopic analysis reveals the porous nature of the soil material. The soil being studied has a solid density, ๐œŒ ๐‘  , of 2.742 g/cm 3 . The minimum and maximum dry densities, ๐œŒ ๐‘š๐‘–๐‘› and ๐œŒ ๐‘š๐‘Ž๐‘ฅ , are 0.600 and 0.696 g/cm 3 , respectively.…”
Section: Materials and Experiments Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…From field practice and laboratory tests, it is widely observed that stress levels sufficient for particle breakage are encountered in deep penetration and compaction, and examples of such situations include displacement pile driving, cone penetration testing in coarse-grained soils and high earth or rockfill dams. Particle breakage is a phenomenon that is commonly observed in offshore engineering practices, occurring in various types of soil particles, including both strong particles like quartz sand, as well as weaker ones such as carbonate or calcareous sands [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%